Adaptive finite‐time stabilization of a class of quantized nonlinearly parameterized systems. (24th April 2017) - Liu, Wenhui; Ho, Daniel W. C.; Xu, Shengyuan; Zhang, Baoyong
Summary: This paper deals with the problem of adaptive control of a class of strict‐feedback nonlinearly parameterized systems with quantized input signal. A hysteretic type of quantizer is used to avoid chattering. By using a power integrator technique, a new controller is designed to ensure the global finite‐time stability of the nonlinear system. Finally, two simulation examples are given to demonstrate the effectiveness of our design method. Copyright © 2017 John Wiley & Sons, Ltd.